COVID-19: Considerations for Children and Families During the Pandemic - Tang, Binzhi; Alam, Didarul; Rakib, Mejbah Uddin; Li, Maojun (Frontiers in Pediatrics, 2021)
Corona Virus Disease 2019 (COVID-19), a fatal virus caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a pandemic across the world. Despite early concerns, children appear to be less susceptible to acquiring SARS-CoV-2 and manifest minor clinical symptoms compared with adults. However there still exists a risk of physical and psychological health problems in children and their families. In this review we summarize the existing information about the mechanism of SARS-CoV-2 infection, the epidemiology of COVID-19, and the clinical manifestations, treatments and further considerations regarding COVID-19 in children.